Effect of noninvasive respiratory support on interstitial lung disease with acute respiratory failure: A systematic review and meta-analysis - Natthawan Sanguanwong; Nattawat Jantarangsi; Jinjuta Ngeyvijit; Natthida Owattanapanich; Vorakamol Phoophiboon (Canadian Journal of Respiratory Therapy)
# Background